Alzheimer’s Disease detection and classification using transfer learning techniques and ensembling operations on convolutional neural networks - Awwal, Alvina; Shomee, Homaira Huda; Sadat, Sayed Us; Amin, Sadia Nur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.